THE STRATEGIC ROLE OF SOCIAL STUDIES TEACHERS IN DEVELOPING DEEP LEARNING-BASED CURRICULUM TO FACE THE CHALLENGES OF THE DIGITAL ERA - Junianto, Rino; Jamil; Tutuk Ningsih; Siswadi (SOSIOEDUKASI, 2026)
This study aims to analyze the strategic role of social studies teachers in developing a deep learning-based curriculum to face the challenges of the digital era at SD Negeri Karangcegak, Sumbang District, Banyumas Regency. Digital transformation requires a change in the learning approach from just knowledge transfer to learning that emphasizes conceptual understanding, critical thinking, collaboration, creativity, and the ability to solve social problems. This study uses a qualitative approach with interview, observation, and documentation data collection techniques. The results showed that teachers began to integrate project-based learning, local social case studies, as well as the use of simple digital media to encourage more in-depth learning. The strategic roles carried out by social studies teachers at SDN Karangcegak Sumbang District are (1) as learning designers who design contextual learning oriented to deep understanding; (2) as a facilitator who encourages cognitive engagement through discussion, scaffolding, and critical questioning; (3) as a motivator who builds a learning climate conducive to active student involvement; (4) as an innovator who develops problem-based and project-based learning methods; (5) as a curriculum designer who adapts the national curriculum to the local context; and (6) as an integrative user of contextual learning media and resources.